PERANGKAT PEMBELAJARAN BERBASIS KETERAMPILAN GENERIK SAINS PADA TOPIK KINETIKA KIMIA - Anwar, Muhammad; Side, Sumiati (Universitas Negeri Makassar, 2015)
This research is a development research that aims to produce generic skill-based learning tools on the chemical kinetic topic. Chemical kinetic Topic is a part of the Physical Chemistry II course.. This topic include: kinetic reaction, reaction mechanism, temperature influence on chemistry reaction rates, and photochemistry. Learning tools that developed are: Learning Plan Unit (LPU), Student Worksheet, and Achievement Test. The development model used is the 4-D model of the development of Thiagarajan with four stages, namely: the definition (define), design (design), development (develop), and the spread (disseminate). The validity of the test is based on two validator evaluation. Test the practicality of the tools in this study are lecturers and students of the chemistry education programs of Science and Mathematics Faculty UNM who follow the course of chemical kinetics. Test the effectiveness based on n-gain of student achievement results. The results showed that the learning tools developed have valid criteria.